Enlisting on teacher profesional development: reflections of teachers’ experiences - Zide, Lulama; Mokhele, Matseliso L. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Teachers are the cornerstone of teaching and learning. They hold prominent positions that dictate that schools improve based on their (teachers) skills and abilities. Having high quality teachers is therefore one of the key obligatory elements for the enhancement of quality education hence the need for teachers’ continuing professional development. The purpose of Teachers Continuing Professional Development is to equip teachers with meeting the challenges and demands of not only the democratic South Africa but also globally in the 21st century. The critical issue is however, the fact that much of the literature still show how professional development has not been able to change teachers’ classroom practices and that teachers are mostly not satisfied with the professional development that is offered to them. Using qualitative case study research design, this paper explores in detail the reflections of teachers on continuing professional development programmes. The findings reveal that teachers are not satisfied with their participation due to the poor planning and lack of monitoring of the programmes, which results in the programmes being non-continuous and repetitively leaving no mark of change in the education system as a whole. The paper concludes that non-involvement of teachers in the planning of their professional development results in the above findings. We therefore recommend that, teachers are provided with opportunity to not only attend but also plan the professional development programs that they believe will change their classroom practices.